2019
DOI: 10.23922/jarc.2018-031
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status predicts adjuvant chemotherapy outcomes for stage III colorectal cancer

Abstract: Objectives: Previously, adjuvant chemotherapy using oxaliplatin was a standard treatment for patients with node-positive colorectal cancer (CRC) who underwent curative surgery. The factor predicting adverse events and therapeutic effect have not yet been established. Methods: A retrospective cohort of 42 patients diagnosed with stage III CRC between April 2009 and March 2013 in our institution were included in this study. The indicators of host nutritional status were body weight (BW), body mass index (BMI), s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
(22 reference statements)
4
2
0
1
Order By: Relevance
“…A previous study showed that patients with high OPNI shared a significantly better prognosis than those who had a lower value of OPNI [ 22 ]. Similar results regarding Crohn’s disease and stage III colorectal cancer have also been reported [ 1 , 27 , 28 ]. In our study, the border value of the OPNI was determined to be 42.6 for the TKI-unused group and TKI-unused group according to the survival cut-off analysis in R 3.6.3.…”
Section: Discussionsupporting
confidence: 87%
“…A previous study showed that patients with high OPNI shared a significantly better prognosis than those who had a lower value of OPNI [ 22 ]. Similar results regarding Crohn’s disease and stage III colorectal cancer have also been reported [ 1 , 27 , 28 ]. In our study, the border value of the OPNI was determined to be 42.6 for the TKI-unused group and TKI-unused group according to the survival cut-off analysis in R 3.6.3.…”
Section: Discussionsupporting
confidence: 87%
“…The previous studies showed that patients with high OPNI shared a signi cantly better prognosis than those who had a lower value of OPNI [22]. And similar results regarding Crohn's disease and stage III colorectal cancer have been also reported [27,28]. In our study, the border value of the OPNI was determined to be 42.6 for TKIs-used group and TKIs-unused group according to survival cut-off analysis by R 3.6. lymphocytes play an important role in the host immune response, eliminating tumor formation and progression.…”
Section: Discussionsupporting
confidence: 80%
“…The previous studies showed that patients with high OPNI shared a signi cantly better prognosis than those who had a lower value of OPNI [22]. And similar results regarding Crohn's disease and stage III colorectal cancer have been also reported [27,28]. In our study, the border value of the OPNI was determined to be 42.6 for TKIs-used group and TKIs-unused group according to survival cut-off analysis by R 3.6.…”
Section: Discussionsupporting
confidence: 80%